Digital consulting model in social communication with the productive business system - Argota Pérez, Yadira (2021)
The aim of the study was to represent a digital consulting model in social communication with the productive business system. The digital consulting model establishes three stages called: I) prevention, II) correction and, III) maintenance and surveillance. There are criteria that identify the stages and refer to the analysis of the business context (I), problematic situation (II), continuity of business management for the social communication of the productive business system (III). Seven phases are established that comprise: 1st) description of the legal documentation of the productive business system, 2nd) description of the management of processes and responsibilities, 3rd) exploration of process management, 4th) mode of execution of process management, 5th) analysis of process management, 6th) evaluation of process management and 7th) control of process management and value chain. Three job performance conditions were considered: A) provision of customer service on a digital platform, B) trust in the consultant according to their professional skills and C) interactive benefits of the implemented digital service where the synchronous review of the consulting process determines optimization temporary and makes its difference in relation to traditional consulting. It is concluded that the representation of the digital consulting model in social communication with the productive business system provides benefits.